Psychosocial Perspective on Menopausal Transition to Achieve Psychological Well-Being: Literature Review - Budi Sarasati Barmawi; Setiasih Setiasih; Monique Elizabeth Sukamto (LPPM IAIN Parepare, 2023)
The menopausal transition is a critical phase for psychological disorders such as depression and anxiety, with depression prevalence rates ranging up to 20% during menopause. However, most women are able to overcome this phase well so they look tough. This study aimed to find out psychosocial factors influencing the psychological well-being of women during the menopausal transition. This transition period occurs when women reach the age of 40-54 years, marked by menstrual irregularities until menstruation stops occurring naturally. Most women will experience physical symptoms such as hot flashes, night sweats, and other symptoms. This study used the literature review method with the Google Scholar database for Indonesian language articles and the Science Direct database for English language articles. This process succeeded in collecting 709 articles published in 2013-2023. The results showed that several psychosocial factors influence psychological well-being during the perimenopause period, including vasomotor symptoms (hot flushes, sleep disorders, menstrual disorders, decreased memory, muscle pain, emotional irritability, reduced sexual interest), socio-demographic conditions (single, obesity, smoker, age, occupation), awareness, attitude, self-efficacy, support, education, and stress level. Thus, the research implication shows that understanding the psychosocial factors in the perimenopause phase is important for women, so that they can get through the transition period healthily and prosperously.